2020
DOI: 10.3390/ijms21176434
|View full text |Cite
|
Sign up to set email alerts
|

The Role of MicroRNAs in Arrhythmogenic Cardiomyopathy: Biomarkers or Innocent Bystanders of Disease Progression?

Abstract: Arrhythmogenic cardiomyopathy (AC) is an inherited cardiac disease characterized by a progressive fibro-fatty replacement of the working myocardium and by life-threatening arrhythmias and risk of sudden cardiac death. Pathogenic variants are identified in nearly 50% of affected patients mostly in genes encoding for desmosomal proteins. AC incomplete penetrance and phenotypic variability advocate that other factors than genetics may modulate the disease, such as microRNAs (miRNAs). MiRNAs are small noncoding RN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…While the progression of an ARVC to a BIV variant is already known to be common in ACM natural history, the coexistence of ALVC and ARVC forms even within variant carriers belonging to the same family raises the issue of modifying factors and genes that are not completely known up to now (Figures 2 and 3). [13][14][15][16][17][18]…”
Section: Intrafamilial Clinical Variability In P/lp Dsp Variant Carriersmentioning
confidence: 99%
“…While the progression of an ARVC to a BIV variant is already known to be common in ACM natural history, the coexistence of ALVC and ARVC forms even within variant carriers belonging to the same family raises the issue of modifying factors and genes that are not completely known up to now (Figures 2 and 3). [13][14][15][16][17][18]…”
Section: Intrafamilial Clinical Variability In P/lp Dsp Variant Carriersmentioning
confidence: 99%
“…In particular, myocardial expression of IL-17 and/or TNF is substantially enhanced in all cases of arrhythmogenic cardiomyopathy [ 38 ]. In a large cohort of samples, the miR-122-5p , miR-133b , miR-133a-3p , miR-142-3p , miR-183-5p, and miR-182-5p could possess high diagnostic potential in arrhythmogenic cardiomyopathy patients [ 39 , 40 ]. The implication of miRNAs in the pathogenesis of arrhythmogenic cardiomyopathy has been the objective of multiple studies.…”
Section: Other Cardiac Rhythm Disordersmentioning
confidence: 99%
“…Secondly, Bueno Marinas studied nine ACM cases and four controls (RV tissue and plasma) by means of an 84-miRNA cardiac-related array. After validation in a larger cohort of samples, they concluded that a group of six miRNAs (miR-122-5p, miR-133a-3p, miR-133b, miR-142-3p, miR-182-5p, and miR-183-5p) presented high discriminatory diagnostic power in ACM patients [ 60 ]. Thirdly, Sacchetto et al screened 754 miRNAs in 21 pooled plasmas from ACM patients and 20 controls.…”
Section: Non-coding Rnasmentioning
confidence: 99%